Liberalism as a Philosophy of Culture - Jokubaitis, Alvydas; Jokubaitis, Linas (Problemos, 2018)
[only abstract in English; full article and abstract in Lithuanian]The paper explores the paradoxes of the political philosophy of liberalism. Liberal conception of justice is incapable of providing grounds for an identity of liberalism. Liberals do not have a moral conception of their own. This is a source of a paradox. Political identity points to morality and moral identity points to politics. The aim of this paper is to clarify this paradox. Political liberalism is based on certain assumptions of a philosophy of culture. Liberals defend a conception of culture which justifies their inconsistencies. They lack any coherent conception of morality and politics. The article is an attempt to prove this by using the “final position” – an alternative to the Rawlsian “original position”.
Keywords: liberalism, John Rawls, original position, final position, philosophy of culture, human nature and politics